Nucleotide Binding Modes in a Motor Protein Revealed by 31P‐ and 1H‐Detected MAS Solid‐State NMR Spectroscopy. (30th September 2019) - Wiegand, Thomas; Schledorn, Maarten; Malär, Alexander A.; Cadalbert, Riccardo; Däpp, Alexander; Terradot, Laurent; Meier, Beat H.; Böckmann, Anja
Abstract: Protein–nucleic acid interactions play important roles not only in energy‐providing reactions, such as ATP hydrolysis, but also in reading, extending, packaging, or repairing genomes. Although they can often be analyzed in detail with X‐ray crystallography, complementary methods are needed to visualize them in complexes, which are not crystalline. Here, we show how solid‐state NMR spectroscopy can detect and classify protein–nucleic interactions through site‐specific 1 H‐ and 31 P‐detected spectroscopic methods. The sensitivity of 1 H chemical‐shift values on noncovalent interactions involved in these molecular recognition processes is exploited allowing us to probe directly the chemical bonding state, an information, which is not directly accessible from an X‐ray structure. We show that these methods can characterize interactions in easy‐to‐prepare sediments of the 708 kDa dodecameric DnaB helicase in complex with ADP:AlF4 − :DNA, and this despite the very challenging size of the complex. Abstract : Protein–nucleotide contacts in a noncrystalline bacterial DnaB helicase sedimented in the NMR rotor were probed by 31 P‐ and 1 H‐detected solid‐state NMR spectroscopy. The sensitivity of 1 H chemical shifts to hydrogen bonding was explored and used to identify residues involved in nucleotide coordination.